CPC-086 Miglustat Off-Label in a Paediatric Formulation For a Rare Metabolic Disease: Early Infantile GM1 Gangliosidosis. (12th March 2013) - Garzone, A; Pompilio, A; Ciuccarelli, F; Andresciani, E; Ficcadenti, A; De Meo, M; Mannucci, A; Marzioni, P; Buccolini, M; Carloni, L; Pinto, F; Moretti, V
Abstract : Background: GM1 gangliosidosis, a rare metabolic disease, is an autosomal recessive lysosomal storage disorder caused by a deficiency of beta-galactosidase, and characterised by the generalised accumulation of GM1 ganglioside. The most severe form, called type I or early infantile, progressively destroys the neurons and the cells of the spinal cord. No pharmacological treatment is available at present and children affected by GM1 type I usually do not survive past the age of three. Miglustat (N-butyldeoxynojirimycin) is an iminosugar and functions as a competitive and reversible inhibitor of glucosylceramide synthase, the initial enzyme in reactions resulting in the synthesis of most glycosphingolipids. It is indicated in lysosomal storage diseases and it had positive results in GM2 gangliosidosis. Purpose: To describe our experience in the 12-month treatment with an individual formulation of miglustat, for a patient affected by GM1 gangliosidosis. Materials and Methods: In July 2011 Regione-Marche Centre for Rare Diseases involved our Hospital Pharmacy (authorization, galenic compounding) in supplying miglustat for an 18-month-old child with type I GM1 gangliosidosis, who was clearly showing severe signs of the pathology, lacking any other therapy. Miglustat is off-label for this indication, so the approval of the Ethics Committee was necessary with the duty to report results every three months. Personalized capsules were prepared for the hospital and home administration, with different doses (from 30 mg/d to 210 mg/d in 3 doses). The capsules were prepared from Zavesca, exclusively using mannitol as excipient: lactose is to be avoided in GM1 gangliosidosis Results: Miglustat provided surprising results, but only in the first four weeks of treatment. Frequent infections and seizures, typical of the disease, occurred later. Conclusions: The treatment is still being used, but after 12 months, we are considering stopping it. It would be important to compare other experiences in order to better evaluate the effectiveness of the treatment. No conflict of interest.